Attachment to God: A Qualitative Exploration of Emerging Adults' Spiritual Relationship with God. Issue 3 (September 2013) - Kimball, Cynthia N.; Boyatzis, Chris J.; Cook, Kaye V.; Leonard, Kathleen C.; Flanagan, Kelly S.
This study assessed emerging adults' attachment relationships with parents, peers, and God to explore the sufficiency of the correspondence and compensation models of attachment. We analyzed narratives of 119 (60 male) Christian college graduates describing their relational experiences with God. Narratives were coded for five relational patterns in attachment relationships (Granqvist & Kirkpatrick, 2008). Participants also completed the IPPA scale and were categorized into high or low secure parental and peer attachment groups. No significant differences were found between peer and parental attachment so peer attachment was dropped from further analysis. All of the relational attachment patterns appeared in participant narratives. Perceiving God as Stronger and Wiser appeared most often in both high and low secure parental narratives; Safe Haven and Secure Base also appeared in both attachment groups' narratives. Importantly, emerging adults with low parental security nevertheless articulated reciprocal experiences of secure, intimate attachment with God, suggesting refinement in the correspondence and compensation models to include the potential for a spiritual relationship with God that serves a corrective or reparative role.